PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PENGELOLAAN HIPERTENSI MELALUI EDUKASI DAN SENAM LANSIA - Ulfa Diya Atiqa; Ismi Irfiyanti Fachruddin; Sakinah Amir; Syamsuriah; Andi Hardianti ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2025)
The elderly population is at high risk of developing hypertension, a condition that significantly impairs their quality of life if not properly managed. This community engagement project aimed to enhance the knowledge and self-management skills of older adults in handling hypertension through structured education and adapted physical activity. The intervention consisted of blood pressure screenings, interactive health education using visual media, and tailored elderly exercise sessions conducted at a local clinic. Findings revealed that 55% of participants were hypertension, while educational sessions effectively improved participants’ awareness of risk factors, prevention strategies, and lifestyle modification. The exercise sessions promoted not only physical activity but also social interaction, contributing to psychological well-being. This integrated approach within a community-clinical setting demonstrates its potential as an effective and sustainable model for non-pharmacological hypertension management among older adults